KECURANGAN LAPORAN KEUANGAN DALAM PERSPEKTIF FRAUD DIAMOND THEORY: STUDI EMPIRIS PADA PERUSAHAAN SUB SEKTOR TRANSPORTASI DI BURSA EFEK INDONESIA - M. ADAM PRAYOGA; EKA SUDARMAJI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2019)
This study aims to obtain empirical evidence in detecting fraudulent financial statements from the perspective of 'fraud diamond theory'. The proxy variables used in this study are the influence of pressure, opportunity, rationalization, and ability. This study uses a sample of transportation sub-sector companies listed on the Indonesia Stock Exchange (IDX) with the 2015-2017 research period. This research is expected to contribute to the development of accounting science, especially in the field of forensic accounting regarding factors that can affect companies to conduct fraudulent financial statements by implementing indicators of diamond fraud. Hypothesis testing used multiple linear regression analysis with the help of application eviews software, to help process research data in the form of panel data. The results of this study indicate that pressure, opportunity, rationalization, and ability together were not significantly influence the tendency of fraudulent financial statements.